2015
DOI: 10.1002/pro.2746
|View full text |Cite
|
Sign up to set email alerts
|

Hypothetical protein CT398 (CdsZ) interacts with σ54 (RpoN)‐holoenzyme and the type III secretion export apparatus in Chlamydia trachomatis

Abstract: A significant challenge to bacteriology is the relatively large proportion of proteins that lack sufficient sequence similarity to support functional annotation (i.e. hypothetical proteins). The aim of this study was to apply protein structural homology to gain insights into a candidate protein of unknown function (CT398) within the medically important, obligate intracellular bacterium Chlamydia trachomatis. C. trachomatis is a major human pathogen responsible for numerous infections throughout the world that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 79 publications
(97 reference statements)
0
22
0
Order By: Relevance
“…C. trachomatis CT398 has structural similarity to the Helicobacter flagellar protein FlgZ [6]. This study further revealed interactions of CT398 with the alternative sigma factor RpoN, raising the possibility that CT398 could modulate activity of RNAP.…”
Section: Interactions With Development and Shutting Off Secretion mentioning
confidence: 77%
“…C. trachomatis CT398 has structural similarity to the Helicobacter flagellar protein FlgZ [6]. This study further revealed interactions of CT398 with the alternative sigma factor RpoN, raising the possibility that CT398 could modulate activity of RNAP.…”
Section: Interactions With Development and Shutting Off Secretion mentioning
confidence: 77%
“…Late genes are regulated either by a stage-specific sigma factor (σ 28 ) 19 or through the relief of transcriptional repression of σ 66 -dependent promoters by the repressor early upstream open reading frame (EUO) 19,23 . Transcriptional regulation is also coupled to the T3SS 2426 . Much of this insight comes from in vitro studies; advances in chlamydial genetics (BOX 2) will enable the analysis of current models in vivo .…”
Section: The Developmental Cyclementioning
confidence: 99%
“…A standard BLAST (Altschul et al, 1990) search against the PDB using the MSMEG_4306 sequence as a query did not result in any significant structural homologue that could be used as a template for solving the structure by the molecularreplacement method. However, a DELTA-BLAST (domain enhanced lookup time accelerated BLAST) search (Boratyn et al, 2012) revealed two crystal structures, namely those of HP0958 from Helicobacter pylori (Caly et al, 2010) and CT398 from Chlamydia trachomatis (Barta et al, 2015), as close homologues of MSMEG_4306, although they share only 15% identity with MSMEG_4306. Since the two homologues are likely to be too distantly related for successful molecular replacement, we decided to solve the structure of MSMEG_ 4306 by experimental phasing.…”
Section: Structure Determination and Quality Of The Model Of Msmeg_4306mentioning
confidence: 99%
“…The top two hits were CT398 from C. trachomatis (PDB entry 4ilo,r.m.s.d. 3.8 Å , Z-score 15.9, 229 aligned C atoms; Barta et al, 2015) and HP0958 from H. pylori (PDB entry 3na7, r.m.s.d. 7.7 Å , Z-score 15.6, 230 aligned C atoms;Caly et al, 2010), which appeared to be strikingly similar to the structure of MSMEG_4306 (Fig.…”
Section: Comparison Of Msmeg_4306 With Other Structuresmentioning
confidence: 99%
See 1 more Smart Citation